2011
DOI: 10.1111/j.1552-6569.2011.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Trevo System: Single‐Center Experience with a Novel Mechanical Thrombectomy Device

Abstract: Recent reports have indicated that mechanical thrombectomy may have the potential to treat acute ischemic stroke. This study aims to describe the safety and effectiveness of Trevo Retriever, using Stentriever technology, in revascularization of patients with acute ischemic stroke. METHODSProspective study evaluating the clinical, radiological, and functional outcome of 13 patients with an angiographically verified occlusion of the anterior cerebral circulation. All patients underwent thrombectomy with TR as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…Favorable clinical outcome (defined as mRS, 0 -2) ranged from 36% up to 74%. [10][11][12][13][14][15][16][17][18][19] The present study showed that the prevalence of recanalization and favorable outcome in patients treated by endovascular sonolysis in combination with local or systemic thrombolysis (and cPTAS if indicated) was comparable with (or even superior to) other endovascular methods, especially in patients with MCA occlusion. Moreover, it seemed to be safer.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Favorable clinical outcome (defined as mRS, 0 -2) ranged from 36% up to 74%. [10][11][12][13][14][15][16][17][18][19] The present study showed that the prevalence of recanalization and favorable outcome in patients treated by endovascular sonolysis in combination with local or systemic thrombolysis (and cPTAS if indicated) was comparable with (or even superior to) other endovascular methods, especially in patients with MCA occlusion. Moreover, it seemed to be safer.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to pharmacologic methods, especially IV thrombolysis and intraarterial thrombolysis, mechanical neurointerventional methods ( [10][11][12][13][14][15][16][17][18][19] One of these, the EkoSonic Endovascular System, is the first tool system approved by the FDA that allows local endovascular application of high-frequency (2 MHz) and low-power (400 W/cm 2 ) sonography in clinical practice with or without simultaneous catheter-directed thrombolysis by application of thrombolytic drugs. [22][23][24] Several in vitro, in vivo, and clinical studies have shown the potential effect of sonography (sonolysis) to accelerate clot lysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TV was designed to facilitate proper visualization of the complete device by integrating the platinum wires into the stent struts itself (16)(17)(18). Full structural visibility of the stent during deployment and retrieval allow procedural adaptation or modification by enhancing the operator's understanding of the actual stent-clot or stent-vessel interaction (16).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, SICH occurred in 10% of the prourokinase group [3]. On the other hand, in last years the use of several endovascular thrombectomy devices (Merci®, Trevo® or Solitaire®) has been approved by regulatory agencies [4,5]. The Solitaire retriever has recently been tested in a multicenter study showing REC in 85% of occlusions and good outcome in 55% [6].…”
Section: Introductionmentioning
confidence: 99%